Genetic variation in fenugreek (Trigonella foenum-graecum L.) for phosphorus utili- zation under Aridisol - Poonam Joshi, J C Tarafdar, Indira Rathore, O P Aishwath (Journal of Spices and Aromatic Crops, 2009)
An experiment was conducted at Ajmer (Rajasthan) to investigate the genetic variation ofseven fenugreek (Trigonella foenum-graecum) genotypes for phosphorus utilization under typicalAridisol. The result showed that cv. Rajendra Kranti was superior and could utilize about71% of the rhizosphere phosphorus. A strong positive correlation between plant phosphorusconcentration and alkaline phosphatase (r = 0.51, P < 0.05) as well as dehydrogenase activity(r = 0.62, P < 0.01) in the rhizosphere was observed. Labile phosphorus showed a strongnegative correlation with plant phosphorus concentration (r = -0.70, P < 0.01) and totalphosphorus uptake (r = -0.62, P < 0.01). Higher phosphorus concentration (3.36 mg g-1),total phosphorus uptake (87.4 mg plant -1) and dry biomass (26.0 g plant-1) at critical growthstage was observed in Rajendra Kranti. A strong correlation (r = 0.98, P < 0.001) was alsofound with dry biomass and total phosphorus uptake.